LEGAL CERTAINTY FOR INVESTORS ON INVESTMENT IN THE FIELD OF GEOTHERMAL ENERGY ONLINE BUSINESS - Abdul Rohman Nasution (Problematika Hukum, 2015)
This research discusses about how the role of the state to provide the legal certainty for investor in the field of geothermal energy. As one of the potential energy derived from the natural resources in Indonesia, geothermal should be developed for the welfare of the Indonesian people. In accordance with the mandate of the 1945 Constitution in its preamble stated that the purpose of the state is to improve the welfare of the community. Government guarantees for investors of practice in the field of geothermal energy. Legislation issued by the government to provide legal certainty for investors in capital plant in Indonesia such as: a. Law No. 23 of 2003 about Geothermal b. Law No. 25 of 2007 about Investment c. Law No. 30 of 2007 about Energy Indonesia has a wealth of energy resources. One of the energy resources owned by Indonesia is geothermal energy. However, in the development and utilization of geothermal energy, the implementations of energy sources are yet to be optimized to the maximum by the government. Keywords : legal certainty, investment, investor, geothermal energy. Penelitian ini membahas tentang bagaimana peran negara untuk memberikan kepastian hukum bagi investor di bidang energi panas bumi. Sebagai salah satu energi potensial yang berasal dari sumber daya alam di Indonesia, panas bumi harus dikembangkan untuk kesejahteraan masyarakat Indonesia. Sesuai dengan amanat UUD 1945 dalam pembukaannya menyatakan bahwa tujuan negara adalah untuk meningkatkan kesejahteraan masyarakat. jaminan pemerintah bagi investor praktek di bidang energi panas bumi. Legislasi yang dikeluarkan oleh pemerintah untuk memberikan kepastian hukum bagi investor di pabrik modal di Indonesia seperti: a. Undang-Undang Nomor 23 Tahun 2003 tentang Panas Bumi b. Undang-Undang Nomor 25 Tahun 2007 tentang Penanaman Modal c. Undang-Undang Nomor 30 Tahun 2007 tentang Energi Indonesia memiliki kekayaan sumber daya energi. Salah satu sumber energi yang dimiliki oleh Indonesia adalah energi panas bumi. Namun, dalam pengembangan dan pemanfaatan energi panas bumi, implementasi sumber energi yang belum dioptimalkan secara maksimal oleh pemerintah. Kata kunci: kepastian hukum, investasi, investor, energi panas bumi. Key word: Geothermal Energy